Maluję rzekę Bug - Baj, Stanisław (Załącznik Kulturoznawczy, 2023)
This draft is a record of the aesthetic and creative experiences associated with the Bug River. The author, who is a painter himself, proves that the oil technique is unique in terms of the possibility of achieving an effect of a flowing water. In the faint panes of the river you can see unusual emanations of light and improbable, delicate traces of distraction of its action. This unreal water structure of the Bug River is always vertical. For an oil painter, it is an important inspiration to reflect that rhythm of water in a suitable pattern of canvas paint, using its consistency, thickness, texture.